1996
DOI: 10.1289/ehp.961041165
|View full text |Cite
|
Sign up to set email alerts
|

An overview of benzene metabolism.

Abstract: Benzene toxicity involves both bone marrow depression and leukemogenesis caused by damage to multiple classes of hematopoietic cells and a variety of hematopoietic cell functions. Study of the relationship between the metabolism and toxicity of benzene indicates that several metabolites of benzene play significant roles in generating benzene toxicity. Benzene is metabolized, primarily in the liver, to a variety of hydroxylated and ring-opened products that are transported to the bone marrow where subsequent se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(47 citation statements)
references
References 48 publications
1
46
0
Order By: Relevance
“…It was reported that some of gasoline vapors components are haematotoxic in humans (workers subjected to benzene, toluene and xylene) [15,16] and the same observation was reported in experimental animals (rats exposed to gasoline vapors) [17]. In the present study, gasoline 80 inhalation significantly reduced the PCV in treated male rats.…”
Section: Discussionsupporting
confidence: 88%
“…It was reported that some of gasoline vapors components are haematotoxic in humans (workers subjected to benzene, toluene and xylene) [15,16] and the same observation was reported in experimental animals (rats exposed to gasoline vapors) [17]. In the present study, gasoline 80 inhalation significantly reduced the PCV in treated male rats.…”
Section: Discussionsupporting
confidence: 88%
“…2010; IARC 2011). Briefly, benzene is metabolized to several reactive metabolites that can damage hematopoietic progenitor cells and lead to depression of the bone marrow (Ross 2000; Snyder and Hedli 1996; Wang et al 2012). This hematopoietic damage is upstream of blood cell formation and can manifest as reduced blood cell counts (cytopenia) and altered hematologic parameters, while prolonged exposure can lead to hematologic conditions including aplastic anemia, leukemia, and other hematologic cancers (ATSDR 2007a; Galbraith et al 2010; IARC 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism by which benzene induces leukemia is as yet unresolved and remains an area of intensive research [39- 41]. The metabolism of benzene is complex [42], generating numerous DNA reactive intermediates, phenols and quinones that can react with DNA directly, or generate DNA reactive oxygen species [43]. Although the metabolism of benzene to DNA-reactive intermediates is required for leukemogenesis, most of the products produced are weak mutagens per se .…”
Section: Introductionmentioning
confidence: 99%